Strategi Guru PAI dalam Penguatan Moderasi Beragama di SMKS 17 Budi Mulya Kota Bengkulu - Abdul Malik Aziz; Nurlaili Nurlaili; Khairiah Khairiah (UIN Fatmawati Sukarno Bengkulu, 2022)
Islamic Religious Education Teachers' Strategy in Strengthening Religious Moderation, Postgraduate Islamic Religious Education Study Program, Fatmawati Sukarno State Islamic University, Bengkulu, Supervisor Dr. Nurlaili, S.Ag., M.Pd., Dr. Hj. Khairiah, M.Pd.I Indonesia is a country with full diversity in terms of religion, language, and ethnicity. In the midst of this diversity, a religious method is needed that prioritizes balance, religious moderation is the answer to problems that arise due to the exclusive attitudes of certain groups, in strengthening religious moderation, educational institutions are the spearhead, the success of religious moderation can be measured by how serious educational institutions are in developing strategies to strengthen religious moderation, especially in Islamic Religious Education learning. Islamic religious education which believes that religious life itself prioritizes balance between religion and life, it is only natural that an Islamic Religious Education teacher can help accelerate the strengthening of religious moderation both in terms of attitudes of tolerance, anti-violence, national commitment and. accommodating to local culture which are indicators of religious moderation. This study focuses on how Islamic Religious Education teachers develop strategies to strengthen religious moderation in the midst of the lives of students at vocational high school 17 Budi Mulya, Bengkulu City, schools that have a heterogeneous environment need to have special strategies to avoid students from extreme traits that are contrary to the principles of religious moderation Keywords: Strategy, Islamic Religious Education, Religious Moderation